Pro MySQL - Kruckenberg, Michael; Pipes, Jay.; SpringerLink (Online service) (Berkeley, CA : Apress, 2005)
Pro MySQL is the first book that exclusively covers intermediate and advanced features of MySQL, the world's most popular open source database server. Whether you are a seasoned MySQL user looking to take your skills to the next level, or youre a database expert searching for a fast-paced introduction to MySQL's advanced features, this book is for you. The first part of this book discusses topics related to design and development. Topics include transaction processing and indexing theory, benchmarking and profiling, and advanced coverage of storage engines and data types. The authors also delve deep into the MySQL source code and system architecture at a level you won't find anywhere else. Essential advanced SQL is also covered, with discussion of subqueries, derived tables, and joins. These concepts are demonstrated in a range of situation-specific examplesfrom dealing with hierarchical data to performing geographic information system (GIS) examples with just MySQL. This section also covers MySQL 5's new enterprise features like stored procedures, triggers, and views. The latter part of this book devotes itself to administration topics. Topics include MySQL installation and upgrading, user administration, database backups, replication, and clustering. You'll also learn about the new data dictionary features available in MySQL 5.
Design and Development -- Analyzing Business Requirements -- Index Concepts -- Transaction Processing -- MySQL System Architecture -- Storage Engines and Data Types -- Benchmarking and Profiling -- Essential SQL -- SQL Scenarios -- Stored Procedures -- Functions -- Cursors -- Views -- Triggers -- Administration -- MySQL Installation and Configuration -- User Administration -- Security -- Backup and Restoration -- Replication -- Cluster -- Troubleshooting -- MySQL Data Dictionary.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books